ANALISIS DAN KAJIAN MODEL-MODEL PENGEMBANGAN KURIKULUM DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH - Zidan El Zaldie; Ma’mun Hanif; Maksum; Heida Rahma Eksanti; Wafda Sabilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relevance of classical curriculum development models, namely Tyler, Hilda Taba, Oliva, and Miller-Seller, to the implementation of the Merdeka Curriculum in schools. The study employed a descriptive qualitative approach using library research and case study methods. Data were collected from books, scientific journals, official government documents, and other reliable sources, and were analyzed using content analysis techniques through theme categorization, data comparison, and conclusion drawing. The findings indicate that the Merdeka Curriculum is closely related to these classical curriculum development models. Tyler's model is relevant to the formulation of learning objectives and evaluation, Hilda Taba's model aligns with differentiated learning and the active role of teachers, Oliva's model supports systematic school curriculum management, while the Miller-Seller model is relevant to character development through the Projek Penguatan Profil Pelajar Pancasila (P5). The successful implementation of the Merdeka Curriculum is also influenced by teacher readiness, school leadership, a collaborative culture, and the availability of facilities and infrastructure. Therefore, it can be concluded that the integration of Tyler, Hilda Taba, Oliva, and Miller-Seller models can strengthen the implementation of the Merdeka Curriculum, making it more structured, flexible, and capable of producing intelligent, creative, critical, and well-characterized learners who are prepared to meet the demands of the 21st century.